Sejarah Pendidikan di Indonesia Pasca Orde Baru dan Tantangannya Menghadapi Era Disrupsi - Sayyida Safir Fadhila; Muhammad Miftah (IAIN Ponorogo, 2024)
After the fall of the New Order in 1998, Indonesia experienced a major transformation in various aspects of life, one of which was the Islamic education system. The political changes and reforms that occurred had a significant influence on the way Islamic education was managed and developed. In this era of disruption triggered by technological advances, globalization, and Islamic educational institutions such as Islamic boarding schools and madrasas are facing unique and complex challenges. The research aims to understand Islamic education in Indonesia after the New Order and identify and evaluate the challenges faced by Islamic education institutions in the era of disruption. As well as knowing the role of Islamic educational institutions which remain relevant and effective in the modern context. The research method applied is a literature study by examining various literature sources. The results of this research are to improve the quality of Islamic education, equip students with optimal mastery of science and technology supported by a good religious and social mentality, and create a good and true generation of people. The era of disruption presents challenges to the digital divide, as well as the need to balance traditional values ​​and modern innovation.